Experimental and Analytical Study of Bending Stresses and Deflections in Curved Beam Made of Laminated Composite Material - Ismail, Assma Hassan (Al-Khwarizmi Engineering Journal, 2017)
Abstract Theoretical and experimental methodologies were assessed to test curved beam made of layered composite material. The maximum stress and maximum deflection were computed for each layer and the effect of radius of curvature and curve shape on them. Because of the increase of the use of composite materials in aircraft structures and the renewed interest in these types of problems, the presented theoretical assessment was made using three different approaches: curved beam theory and an approximate 2D strength of material equations and finite element method (FEM) analysis by ANSYS 14.5 program for twelve cases of multi-layered cylindrical shell panel differs in fiber orientations and number of layers. One case of E-glass composite material was experimentally made and tested to verify the relation between applied load and maximum deflection and four models were made of poly carbonyl to determine stresses under bending loads in polar scope, all results were compared with each other, the percentage accuracy was very good. The curved beam theory and strength of material equation formulas results were reasonable for the bottom surface, while it seems not enough for the top surfaces. Also, results explained positions and cases more affected by delaminating and the most preferred part of ellipse shape beam in resisting loads.